2019
DOI: 10.1103/physrevd.100.104031
|View full text |Cite
|
Sign up to set email alerts
|

Relativistic deformed kinematics from momentum space geometry

Abstract: We present a way to derive a deformation of special relativistic kinematics (possible low energy signal of a quantum theory of gravity) from the geometry of a maximally symmetric curved momentum space. The deformed kinematics is fixed (up to change of coordinates in the momentum variables) by the algebra of isometries of the metric in momentum space. In particular, the wellknown example of κ-Poincaré kinematics is obtained when one considers an isotropic metric in de Sitter momentum space such that translation… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
144
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 65 publications
(148 citation statements)
references
References 29 publications
2
144
2
Order By: Relevance
“…Also, we consider that the momentum space tetrad do not change under such transformation. In the following, we will prove that with the definition of the new momentum metric given in this work, starting with a momentum space metric, we can still define momentum transformations for a fixed space-time point x that leave invariant the form of the metric, taking into account the curvature of the spacetime (the generalization to curved spacetime of the results obtained in [23]): there are still 10 momentum isometries of the metric that correspond to the four translations and six transformations that leave the origin invariant (the point in phase space (x, 0)), and we can identify the squared distance from a point in the momentum space to the origin as the deformed dispersion relation. In Appendix A it is shown that when the starting momentum space metric is of constant curvature (maximally symmetric space), the momentum scalar of curvature given by the contraction of Eq.…”
Section: B Curved Momentum and Space-time Spacesmentioning
confidence: 87%
See 4 more Smart Citations
“…Also, we consider that the momentum space tetrad do not change under such transformation. In the following, we will prove that with the definition of the new momentum metric given in this work, starting with a momentum space metric, we can still define momentum transformations for a fixed space-time point x that leave invariant the form of the metric, taking into account the curvature of the spacetime (the generalization to curved spacetime of the results obtained in [23]): there are still 10 momentum isometries of the metric that correspond to the four translations and six transformations that leave the origin invariant (the point in phase space (x, 0)), and we can identify the squared distance from a point in the momentum space to the origin as the deformed dispersion relation. In Appendix A it is shown that when the starting momentum space metric is of constant curvature (maximally symmetric space), the momentum scalar of curvature given by the contraction of Eq.…”
Section: B Curved Momentum and Space-time Spacesmentioning
confidence: 87%
“…In this section we will first review the main results of [23]. We will expose how a deformed relativistic kinematics can be understood through a maximally symmetric momentum space, characterized by a metric g µν k (k).…”
Section: Metric In the Cotangent Bundlementioning
confidence: 99%
See 3 more Smart Citations